2021
DOI: 10.1002/tpg2.20113
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, population structure, and linkage disequilibrium among cowpea accessions

Abstract: Cowpea [Vigna unguiculata (L.) Walp] is a globally important food security crop.However, it is susceptible to pest and disease; hence, constant breeding efforts based on its diversity are required for its improvement. The present study aims to investigate the genetic diversity, population structure, and linkage disequilibrium (LD) among 274 cowpea accessions from different origins. A total of 3,127 single nucleotide polymorphism (SNP) markers generated using diversity array technology (DArT) was used. Populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 64 publications
(110 reference statements)
5
9
2
Order By: Relevance
“…The discovery of markers associated with this trait can help in fast tracking, selection, and breeding of cowpea varieties with high carotenoid content in the sprouts. The results showed that the 125 accessions can be distributed into three groups, which corroborates our previous findings in the population of origin of the accessions [ 31 ]. Although the presence of population structure within the germplasm is a positive indication of genetic potential for improvement, it can be a confounding factor in testing the associations between markers and phenotypic variation [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The discovery of markers associated with this trait can help in fast tracking, selection, and breeding of cowpea varieties with high carotenoid content in the sprouts. The results showed that the 125 accessions can be distributed into three groups, which corroborates our previous findings in the population of origin of the accessions [ 31 ]. Although the presence of population structure within the germplasm is a positive indication of genetic potential for improvement, it can be a confounding factor in testing the associations between markers and phenotypic variation [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 90%
“…The genomic data used in this study consisted of 3,120 SNPs markers ( Table S3 ), previously reported among a diversity panel of cowpea [ 31 ], which includes the 125 accessions used in the present study. The genetic diversity parameters of the germplasm were estimated in GenAlex [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 4,957 high-quality selected SNPs were polymorphic as observed in previous SNP-based genetic diversity studies in Dioscorea alata [3] and Dioscorea rotundata [28]. Similar polymorphism values have also been reported in several important food crops such as oilseed crop (0.21) [46], soybean (0.28) [47], rice (0.31) [48], maize (0.19) [49], cowpea (0.24) [50], common bean (0.25) [51] and chickpea (0.32) [52]. This study also demonstrated the possibility of using the selected DArTseq-SNP markers for genomic investigations in yams, which may serve as a foundation for future breeding efforts in Uganda and conservation initiatives in the country.…”
Section: Plos Onesupporting
confidence: 78%